Mosaic trisomy 2 at amniocentesis: Prenatal diagnosis and molecular genetic analysis - Chih-Ping Chen; Yi-Ning Su; Schu-Rern Chern; Yu-Ting Chen; Peih-Shan Wu; Jun-Wei Su; Chen-Wen Pan; Wayseen Wang (Elsevier, 2012)
Objective: This study aims at presenting prenatal diagnosis of mosaic trisomy 2 and reviewing the literature. Materials, Methods, and Results: A 32-year-old woman underwent amniocentesis at 21 weeks of gestation because of abnormal maternal serum biochemistry. Amniocentesis revealed a karyotype of 47,XY,+2[1]/46,XY[21] in in situ cultures. The single colony with trisomy 2 had two metaphase cells, and both had the karyotype of 47,XY,+2. Repeated amniocentesis was performed at 23 weeks of gestation. Interphase fluorescence in situ hybridization (FISH) analysis on uncultured amniocytes using a 2q11.1-specific probe RP11-468G5 (spectrum green) showed three green signals in 11 of 47 uncultured amniocytes, indicating 23.4% mosaicism for trisomy 2. The cultured amniocytes had a karyotype of 46,XY[20 colonies]. Polymorphic DNA marker analysis excluded uniparental disomy 2. The woman underwent the third amniocentesis at 25 weeks of gestation. Interphase FISH analysis on uncultured amniocytes revealed 9.4% (5/53 cells) mosaicism for trisomy 2. The cultured amniocytes had a karyotype of 46,XY[30 colonies]. Prenatal ultrasound was normal. The parents decided to continue the pregnancy to term, and a 3316-g baby was delivered with no phenotypic abnormalities. Cord blood had a karyotype of 46,XY[40 cells]. Interphase FISH analysis on uncultured urinary cells revealed 8.2% (4/49 cells) mosaicism for trisomy 2. The neonate was normal in growth and psychomotor development at 6 months of age. Conclusion: Prenatal diagnosis of a single colony with two or more cells with trisomy 2 at amniocentesis should alert a clinically significant aneuploidy, and interphase FISH on uncultured amniocytes is useful for rapid confirmation of low-level trisomy 2 mosaicism at amniocentesis. The abnormal cell line of trisomy 2 may disappear after long-term amniocyte cultures.